Strategi Komunikasi Pemasaran Pada Usaha Kecil Menengah â€œGULO PUANâ€ Di Media Belanja Online - Andia; Hamidah; Muslimin (CV. ITTC INDONESIA, 2023)
Online product marketing uses Instagram and Shopee as media or means of product promotion. Gulo Puan small and medium enterprises sell traditional food products in Rambutan Village which are made from swamp buffalo milk and granulated sugar called Gulo Puan. This business was founded on June 15 2020 by a housewife named Dwi Pratiwi. The purpose of this research is to find out the marketing communication strategies used by small and medium business owners who market their products through the online media Instagram and Shopee so that these products can be recognized by many consumers. The research method used in this study is descriptive qualitative method, data collection techniques carried out by researchers through observation, interviews and documentation. The primary data sources in this study were Dwi Pratiwi who is the owner of a small and medium gulo lady business, Mrs. Dawisa who is a gulo lady maker, and Muhajirin, who is a swamp buffalo breeder in the village of Rambutan. Secondary data sources were obtained through sales documents for Gulo Puan products on online media, Instagram and Shopee owned by Gulo Puan small and medium enterprises. Based on the results of research on marketing communication strategies carried out by small and medium business owners, Gulo Puan in online shopping media is carried out using the marketing mix theory. The researcher concludes that the marketing communication strategy used by Gulo Puan small and medium business owners in online media is to use the marketing mix theory, using the 4p, namely product, price, place, and promotion (promotion).